2022
DOI: 10.1101/2022.09.30.510271
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A primary rodent triculture model to investigate the role of glia-neuron crosstalk in regulation of neuronal activity

Abstract: Neuroinflammation and hyperexcitability have been implicated in the pathogenesis of neurodegenerative disease, and new models are required to investigate the cellular crosstalk involved in these processes. We developed an approach to generate a quantitative and reproducible triculture system that is suitable for pharmacological studies. While primary rodent cells were previously grown in a coculture medium formulated to support only neurons and astrocytes, we now optimised a protocol to generate tricultures co… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 55 publications
1
2
0
Order By: Relevance
“…Additionally, we observed that the spike frequency decreases at a more rapid rate than the number of active channels, suggesting that changes in neural activity can be detected prior to changes in neuron health. This observation can be paralleled to the findings from the recent study that showed a decrease in electrophysiological activity with increasing microglia density in a dose-response manner [54], where higher microglia numbers in the culture lead to increased microglia reactivity, partially mimicking increased reactivity due to the LPS treatment here. This demonstrates that monitoring extracellular recordings from MEAs is a powerful method to non-invasively study the effect of neuroinflammation in vitro, especially when combined with our previously described tri-culture of neurons, astrocytes, and microglia that more faithfully represents the in vivo neuroinflammatory response.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Additionally, we observed that the spike frequency decreases at a more rapid rate than the number of active channels, suggesting that changes in neural activity can be detected prior to changes in neuron health. This observation can be paralleled to the findings from the recent study that showed a decrease in electrophysiological activity with increasing microglia density in a dose-response manner [54], where higher microglia numbers in the culture lead to increased microglia reactivity, partially mimicking increased reactivity due to the LPS treatment here. This demonstrates that monitoring extracellular recordings from MEAs is a powerful method to non-invasively study the effect of neuroinflammation in vitro, especially when combined with our previously described tri-culture of neurons, astrocytes, and microglia that more faithfully represents the in vivo neuroinflammatory response.…”
Section: Discussionsupporting
confidence: 85%
“…Additionally, we saw some evidence that the tri-culture had an increase in spike frequency at DIV 21 as only the tri-culture showed a significant increase in spike frequency between DIV 7 and DIV 21 ( p = 0.0076 vs p = 0.51 for the co-culture), but once again there was no significant difference in spike frequency between the tri- and co-cultures at DIV 21 ( Figure 1d ). A recent study using a similar tri-culture showed a reversed trend, with microglia appearing to reduce spike frequency and other electrophysiological features [54]. However, in that paper, the amount of microglia was increased to 15-25% of the total cell population, which is more than double the number of microglia found in our tri-culture model [32] and the proportions found in vivo [55].…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation